Potencial Evocado Auditivo de Tronco Encefálico com estímulos CE-Chirp® Level Specific e Narrow Band CE-Chirp® Level Specific em lactentes ouvintes - Ormundo, Diego da Silva (2020)
Introduction: ABR is considered the gold standard test in the audiological evaluation of infants up to sixth month of life. Currently, new stimuli are being developed to optimize the triggering and acquisition of neural responses, both in the evaluation of retrocochlear function and in the estimation of auditory sensitivity. Objective: To investigate the clinical results of ABR with the CE-Chirp® LS and NB CE-Chirp® LS stimuli in hearing infants. Method: A group of 18 hearing infants participated in this study, with an average age of 54.6 days on the date of examination. For ABR record, two channel Eclipse EP25 ABR System equipment and a pair of ER-3A insert phones were used. The examination was carried out in a quiet room, with the infants sleeping in natural sleep. The absolute latency and amplitude of waves I, III and V, interpeak intervals I-III, III-V and I-V and interaural difference of wave V and interpeak interval I V were compared between the stimuli Click and CE-Chirp® LS, to 70 dB nHL. With the NB CE-Chirp® LS stimulus, ABR threshold for 500, 1000, 2000 and 4000 Hz frequency were investigated. Results: There was a statistically significant difference between the Click and CE-Chirp® LS stimuli for the variables: absolute latency of wave I, interpeak intervals I-III, III-V and I-V, and amplitude of wave V. The ABR threshold evoked with NB CE-Chirp® LS stimulus was lower than ABR threshold Toneburst obtained in other studies and are lower for frequencies of 2000 and 4000 Hz. As well, they presented similar absolute latencies, independently of the frequency evaluated. Conclusion: The CE-Chirp® LS stimulus proved to be effective in evoking neural responses in hearing infants, and the NB CE-Chirp® LS stimulus evoked ABR threshold with precision and reliability for the frequencies of 500, 1000, 2000 and 4000 Hz